Shrek 2 - Adamson, Andrew; Asbury, Kelly; Vernon, Conrad; Myers, Mike, 1963-; Murphy, Eddie, 1961-; Diaz, Cameron; Andrews, Julie; Banderas, Antonio; Gregson-Williams, Harry; DreamWorks Home Entertainment (Firm); Universal Studios Home Video (Firm) ([United States] : DreamWorks Home Entertainment ; Universal City, CA : Distributed by Universal Studios Home Video, 2004)
Right after Shrek and Princess Fiona's honeymoon, the newly wed couple goes to Princess Fiona's parents for dinner. When a Fairy Godmother discovers Fiona and Shrek are married she reminds the king about a deal they areed on years ago, that Fiona should have married her son, who happens to be Prince Charming. The King then hires a cat named Puss-in-Boots, a sword fighting cat and ogre slayer, to kill Shrek.
Title from disc.
Widescreen.
Special features: technical goofs; "Meet Puss-in-Boots"; filmmaker commentary; the tech of 'Shrek 2'; a sneak peek from DreamWorks animation; DreamWorks Kids : over 20 games and activites including "Save Fiona!" and "Find Puss-in- Boots"; Shrek's music room : Counting Crows music video; sing-along with the Fairy Godmother.
Art director, Steve Pilcher ; editor, Michael Andrews ; music composer, Harry Gregson-Williams ; costume designer, Isis Mussenden ; production designer, Guillaume Aretos ; visual effects supervisor, Ken Bielenberg ; character animator, Cassidy Curtis.
Voices: Mike Myers, Eddie Murphy, Cameron Diaz, Julie Andrews, Antonio Banderas, John Cleese, Rupert Everett, Jennifer Saunders, Aron Warner.
MPAA rating: PG; for some crude humor, a brief substance reference and some suggestive content.
Keywords: Ghouls and ogres -- Juvenile drama; Princesses -- Juvenile drama; Fairy godmothers -- Juvenile drama; Married people -- Juvenile drama; Films for the hearing impaired; Feature films